2023
DOI: 10.3390/jcm12072482
|View full text |Cite
|
Sign up to set email alerts
|

Causal Link between Inflammatory Bowel Disease and Fistula: Evidence from Mendelian Randomization Study

Abstract: Background: Previous observational studies have found that fistulas are common in Crohn’s disease (CD) and less common in ulcerative colitis (UC). However, some patients have a fistula before diagnosis. Based on retrospective analysis, it was not possible to determine whether there was a bi-directional causal relationship between inflammatory bowel disease (IBD) and fistulas. Methods: Data were extracted from the open GWAS database; 25,042 cases and 34,915 controls were included for IBD, and 6926 cases and 30,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…To eliminate LD among the SNPs, clumping process was implemented with R2 < 0.001 and kb = 10,000. The F statistics were calculated using the formula (F = β2/SE2) for each SNP separately [ 14 , 15 ], Subsequently, we confirmed that the F statistic exceeded 10 in order to mitigate any potential effects of weak instrumental variable bias. Figure 1 depicted the study design through a study framework diagram.…”
Section: Methodsmentioning
confidence: 77%
“…To eliminate LD among the SNPs, clumping process was implemented with R2 < 0.001 and kb = 10,000. The F statistics were calculated using the formula (F = β2/SE2) for each SNP separately [ 14 , 15 ], Subsequently, we confirmed that the F statistic exceeded 10 in order to mitigate any potential effects of weak instrumental variable bias. Figure 1 depicted the study design through a study framework diagram.…”
Section: Methodsmentioning
confidence: 77%
“…To eliminate LD between the SNPs, clumping process was implemented with R2 < 0.001 and kb = 10000. The F statistics were calculated using the formula (F = β2/SE2) for each SNP separately [11,12], Subsequently, we con rmed that the F statistic exceeded 10 in order to mitigate any potential effects of weak instrumental variable bias.…”
Section: Instrumental Variable Selectionmentioning
confidence: 99%
“…The quality of life (QoL) of individuals with immunological disorders is not only significantly impacted by physical and biomedical complications, but also by the psychological and psychosocial challenges of these conditions. Disease specific complications include joint deformities, uveitis [1], cardiovascular problems, and osteoporosis for Rheumatoid Arthritis (RA) and Spondylarthritis (SpA) [2], malnutrition [3,4], colorectal cancer [5,6], stenosis [7], and fistulas [8] for Inflammatory Bowel Disease (IBD; Cohn's disease and Ulcerative colitis) and, arthritis [9], cardiovascular diseases [10], and secondary bacterial infections for Psoriasis (PsO) and Hidradenitis Suppurativa (HS) [11]. Psychological issues are often overlapping for the disorders, such as depression, anxiety, stigmatization and social withdrawal [2,11,12] In addition to appropriate medical treatment, it is essential to consider how individuals experience their own health [13].…”
Section: Introductionmentioning
confidence: 99%